Bacteriological Profile and Antibiotic Sensitivity of Neonatal Septicemia Admitted in Neonatal Intensive Care Unit (NICU) of Dhaka Shishu Hospital - Hossain, Md Mosharaf; Mohammad Yusuf, Mir; Md Kamrunzzaman, -; Rahman, Maksudur; Alam, Md Jahangir (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Septicemia in neonates refers to bacterial infection documented by positive blood culture in the first four weeks of life and is one of the leading causes of neonatal mortality and morbidity. Objective: To isolate and identify the bacterial etiologic agents responsible for neonatal sepsis and to determine the susceptibility pattern of isolates in A NICU of Dhaka Shishu (Children) Hospital. Methods: This is a prospective observational study conducted in the NICU from July 2018 to December 2018. Two hundred ninty blood samples were collected and processed from patients in accordance with standard protocols. Antibiotic susceptibility of the isolates was done. Results: Blood culture reports were positive in 9.31% cases. Among the culture positive cases, there were 65.5% males and 34.5% females. Early onset sepsis was present in 74.8% and late onset sepsis was observed in 25.2% of the cases. Best overall sensitivity among Gram negative (Acinetobacter, Klebsiella, Pseudomonas) isolates was to netilmycin (61%), followed by ceftazidim (57%) and amikacin (56%).Gram positive (Staphylococci, streptococci) isolates had sensitivity of 50% to levofloxacin, 50% to ceftriaxon. Conclusion: Gram negative organisms are the leading cause of neonatal sepsis in this study and most of them are resistant to multiple antibiotics. Therefore the results of this study suggest that, surveillance of antimicrobial resistance in our hospital is necessary. DS (Child) H J 2019; 35(2) : 130-134